Peran Perempuan Pesisir Di Dalam Struktur Nafkah Rumah Tangga Pembudidaya Rumput Laut Di Desa Liya Mawi Kecamatan Wangi-Wangi Selatan Kabupaten Wakatobi - Widya Lestari; Yani Taufik; Nur Isiyana Wianti (PekaBuana : Jurnal Ilmiah Teknologi dan Manajemen Perikanan Tangkap, 2023)
The purpose of this study was to determine the role of women based on household type in the household income structure in Liya Mawi Village, South Wangi-Wangi District, Wakatobi Regency. The method used in this study is to use quantitative analysis, with a sampling technique using cluster sampling technique by categorizing respondents based on family type including extended family, nuclear family and widowed family, with a total sample of 36 female seaweed farmers. The results of the study show that women play a major role in terms of saving family income from seaweed activities, and borrowing money for seaweed activities. However, husband and wife hold equal roles in controlling the process of seaweed cultivation and deciding on needs related to seaweed cultivation. Furthermore, based on the type of household, this tendency also occurs in all types of families, both nuclear and extended families, except for the type of widowed family, where all roles are held by the wife as the head of the family